UNIT 1.29 Quantitative Flow Cytometry Measurements in Antibodies Bound per Cell Based on a CD4 Reference. Issue 1 (6th January 2016) - Wang, Lili; Degheidy, Heba; Abbasi, Fatima; Mostowski, Howard; Marti, Gerald; Bauer, Steven; Hoffman, Robert A.; Gaigalas, Adolfas K.
Abstract : Multicolor flow cytometer assays with fluorescently labeled antibodies are routinely used in clinical laboratories to measure the cell number of specific immunophenotypes and to estimate expression levels of specific receptors/antigens either on the cell surface or intracellularly. The cell number and specific receptors/antigens serve as biomarkers for pathological conditions at various stages of a disease. Existing methods and cell reference materials for quantitative expression measurements have not yet produced results that are of wide clinical interest or are instrument‐independent across all fluorescence channels. This unit details a procedure for quantifying surface and intracellular biomarkers by calibrating the output of a multicolor flow cytometer in units of antibody bound per cell (ABC). The procedure includes (1) quality control of the flow cytometer, (2) fluorescence intensity calibration using hard dyed microspheres assigned with fluorescence intensity values, (3) compensation for fluorescence spillover between adjacent fluorescence channels, and (4) application of a biological reference calibrator to establish an ABC scale. The unit also points out current efforts for quantifying biomarkers in a manner that is independent of instrument platforms and reagent differences. © 2016 by John Wiley & Sons, Inc.